2016
DOI: 10.1016/j.csbj.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

MbT-Tool: An open-access tool based on Thermodynamic Electron Equivalents Model to obtain microbial-metabolic reactions to be used in biotechnological process

Abstract: Modelling cellular metabolism is a strategic factor in investigating microbial behaviour and interactions, especially for bio-technological processes. A key factor for modelling microbial activity is the calculation of nutrient amounts and products generated as a result of the microbial metabolism. Representing metabolic pathways through balanced reactions is a complex and time-consuming task for biologists, ecologists, modellers and engineers. A new computational tool to represent microbial pathways through m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
(92 reference statements)
0
4
0
Order By: Relevance
“…Since then, McCarty expanded TEEM to better reflect aerobic oxidations of single-carbon substrates and the acetyl-CoA pathway for carbon uptake. Past studies have demonstrated that the thermodynamics electron-equivalents method (TEEM) works for a broad range of pure cultures and mixed cultures including Araujo et al (2016), Brock et al (2017), González-Cabaleiro et al (2019), Heijnen and Kleerebezem (2010), Marsolek et al (2007), Roden and Jin (2011), Wang et al (2018), Wilson and Kim (2016), Woo et al (2001), Woo and Rittmann (2000), and Zhu et al (2016). This is true because the thermodynamics of microbial reactions depends on the reactants and products of the reactions, not on the identity of microorganisms. (An in-depth discussion is included in the Supporting Information.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, McCarty expanded TEEM to better reflect aerobic oxidations of single-carbon substrates and the acetyl-CoA pathway for carbon uptake. Past studies have demonstrated that the thermodynamics electron-equivalents method (TEEM) works for a broad range of pure cultures and mixed cultures including Araujo et al (2016), Brock et al (2017), González-Cabaleiro et al (2019), Heijnen and Kleerebezem (2010), Marsolek et al (2007), Roden and Jin (2011), Wang et al (2018), Wilson and Kim (2016), Woo et al (2001), Woo and Rittmann (2000), and Zhu et al (2016). This is true because the thermodynamics of microbial reactions depends on the reactants and products of the reactions, not on the identity of microorganisms. (An in-depth discussion is included in the Supporting Information.)…”
Section: Introductionmentioning
confidence: 99%
“…However, TEEM has been successfully adapted to describe microbial stoichiometry and kinetics in a variety of systems, including those focused on anaerobic digestion kinetics, ,, biodegradation of various contaminants including aromatic compounds and pesticides, and chain elongation . Granda et al developed an online tool, MbT-Tool, to expedite TEEM calculations using a variety of electron donors and acceptors.…”
Section: Introductionmentioning
confidence: 99%
“…The biochemical conversions in microbial systems produce changes in the Gibbs energy and all the energy available for the system is distributed between the catabolic and anabolic reactions, influencing the bioconversion stoichiometries. This concept was first introduced by McCarty (McCarty, 1965;Christensen and McCarthy, 1975) and later evaluated by a number of researchers (Heijnen et al, 1992;VanBriesen, 2002;Kleerebezem and Van Loosdrecht, 2010;Araujo et al, 2016;Brock, 2019), comparing the framework with other models describing bacterial growth. The thermodynamic framework has been successfully applied to predict the performance of various heterotrophic bacteria (McFarland and Sims, 1991;Heijnen, 1994) and is considered a reliable evaluation tool for bioprocess design (Tchobanoglous et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Intuitively, a complete model has a number of sub models that take into account the compartmentalized structure of living organisms. Therefore, the intracellular sub model for the individual behaviour-rules for cellular maintenance and biomass synthesis comes from representing the common metabolic pathways expressed in P. denitrificans through an MMR (Araujo Granda et al, 2016a using TEEM (McCarty, 2007;Rittmann and McCarty, 2001). P. denitrificans can survive in ecosystems with fluctuating aerobic and anaerobic conditions, because it can obtain the chemical energy from respiratory metabolism using molecular oxygen or nitrogen oxides dissolved in the medium; thus in aerobic phase conditions it can execute "Aerobic respiration" with O 2 as the e-acceptor and "Nitrate reduction -Dissimilatory" with NO 3…”
Section: Paracoccus Denitrificans Metabolic Pathwaysmentioning
confidence: 99%